Klima 101: A Climate Change Guidebook for Philippine Journalists - Visaya-Abaño, Imelda; Navarro, Rex L.; Pérez, Rosa T. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
Climate change is a complex issue for journalists to report on and for decision makers and the general public to grasp, despite the increasing scientific evidence of this phenomenon and the growing concern over environmental issues.